Joint damage is amplified in rheumatoid arthritis patients with positive thyroid autoantibodies - Chen, Yu-Lan; Lin, Jian-Zi; Mo, Ying-Qian; Liang, Jin-Jian; Li, Qian-Hua; Zhou, Cheng-Jing; Wei, Xiu-Ning; Ma, Jian-Da; Yang, Ze-Hong; Zheng, Dong-Hui; Dai, Lie (PeerJ, 2018)
Background Autoimmune thyroid disease (AITD), which is characterized by an increased presence of thyroid autoantibodies (TAbs), such as antibodies against thyroid peroxidase (TPOAbs) and antibodies against thyroglobulin (TgAbs), has been reported to be associated with rheumatoid arthritis (RA) because AITD and RA both involve autoimmunity. However, few data are available on the incidence of TAbs in Chinese RA patients, and studies on the association between TAbs and joint damage as well as synovitis in RA patients remain sparse. Here, we aimed to evaluate the incidence of TAbs in a consecutive Chinese RA cohort and to investigate whether the elevated presence of TAbs is associated with joint damage and synovitis in RA patients. Methods A total of 125 hospitalized RA patients were consecutively recruited. Clinical data and available synovial tissues were collected at baseline, and TAbs and thyroid function were detected by chemiluminescent immunoassay. Patients who tested positive for TPOAbs or TgAbs were classified as the TAbs-positive group, and patients who tested positive for neither TPOAbs nor TgAbs were recruited as the TAbs-negative group. Disease activity was assessed using DAS28-ESR (the disease activity score in 28 joints and including the erythrocyte sedimentation rate). X-ray assessment of the hand/wrist was performed according to the Sharp/van der Heijde-modified Sharp score (mTSS), and patients with an mTSS score >10 were defined as having radiographic joint damage (RJD). Serial tissue sections were stained immunohistochemically for CD3, CD15, CD20, CD34, CD38, and CD68, and synovitis were assessed according to Krenn’s synovitis score. Results A total of 44 (35%) patients were positive for either TPOAbs or TgAbs. Importantly, there was a significantly greater percentage of patients with RJD in the TAbs-positive group versus the TAbs-negative group (68% vs. 42%, p = 0.005). Compared with the TAbs-negative group, significantly more CD38-positive plasma cells infiltrated the TAbs-positive synovium, and a higher percentage of patients with high-grade synovitis were observed in the TAbs-positive group (5/8, 63% vs. 5/14, 36%). Moreover, RF positivity and disease activity indicators, including TJC28, DAS28-ESR, and CDAI, were significantly higher in the TAbs-positive group (all p < 0.05). Adjusted logistic regression analysis revealed that positive TAbs (OR 2.999, 95% CI [1.301–6.913]; p = 0.010) and disease duration (OR 1.013, 95% CI [1.006–1.019]; p < 0.001) were independently associated with RJD, and an odds ratio of 2.845 (95% CI [1.062–7.622]) was found for RJD in women with positive TAbs (n = 37) compared with those without TAbs (n = 59) (p = 0.038). Conclusion Our data showed that joint destruction was amplified in RA patients with an elevated presence of TAbs, which supports the importance and necessity of TAbs and thyroid function screening and monitoring in RA patient management in clinical practice.
Keywords: Rheumatoid arthritis; Thyroid autoantibodies; Radiographic joint damage